Living on the margin?: The Iron Age communities of Mananzve Hill, Shashi region, South-western Zimbabwe - Nyamushosho, Robert Tendai (Department of Archaeology, 2017)
In conventional reconstructions of the Iron Age archaeology of southern Africa, drylands have long been viewed as marginal landscapes that did not host any significant agropastoral communities in the past. Against this background, this study explores the discourse of dryland marginality in southern Zambezia using the Shashi region as a case study. Archaeological surveys and excavations were conducted to retrieve reliable data for establishing the settlement history and adaptation strategies of Iron Age communities that lived in this landscape. The study was guided by the concepts of vulnerability, adaptation and resilience, as well as landscape archaeology. Results from excavations conducted at Mananzve, one of the surveyed and excavated sites, show that this part of the Shashi region has a long settlement history spanning the Early Iron Age and the Later Iron Age. Analyses of the recovered material culture shows that Iron Age communities that resided at Mananzve adapted various methods of indigenous dryland agriculture to maintain food security. These findings show that adaptation is context-specific and challenge the designation of drylands such as the Shashi region as 'marginal', since that term undermines the adaptive capacity and resilience of Iron Age communities.